Características clínicas de la neuritis óptica en niños (2003)
Objective. To describe the clinical characteristics and the visual prognosis of a group of children affected with optic neuritis. Patients and methods. The clinical charts of patients under 15 years of age with clinical criteria of optic neuritis were revised at the Hospital Universitario San Vicente de Paúl (Medellín, Colombia), in a time span from January 1th 1989 to December 31th 2001. Results. 16 patients fulfilled the clinical criteria of optic neuritis; 50% were male and the overall mean age was 9,4 years. Seven (43,7%) patients had a preceding infectious disease two weeks earlier and only one suffered from varicella four weeks earlier. Decrease in visual acuity was present in 15 (94%) patients; 7 (44%) had headache; 7 (44%) had ocular ache and 25% had both, head and ocular ache. Neuritis was found in 28 eyes, of whom 68% had papilledema and in 32% the fundoscopic examination was normal. Bilateral affection was present in 75%. Excellent visual prognosis (20/20) was present in 19 (68%) of affected eyes; good (20/20 to 20/50) in 4 (14%), regular (20/50 to 20/100) in 2 (7%) and bad (20/200) in 11%. Conclusion. In our country the clinical evolution of childhood optic neuritis does not differ from that reported in other parts of the world. [REV NEUROL 2003; 36: 208-11]